Perceptions and practices on antimicrobial use by the farmers of the Chikomba District, Zimbabwe - Anderson Munengwa; Chikumba Nation; Mugoti Alban (Aceh Journal of Animal Science, 2020)
Knowledge, attitudes, and practices (KAP) on antimicrobial use (AMU) of livestock farmers are poorly understood in Zimbabwe despite their essence in combating the development of antimicrobial resistance. The aim of the study was to assess these patterns based on suggested KAP variables. A questionnaire-based survey of (n=60) Small Scale Commercial Farmers (SSCF), (n=60) Large Scale Commercial farmers (LSCF), and (n=60) resettled farmers (A1) was undertaken from January to March 2019. Participants were purposively selected from 10 wards based on willingness to participate in the study. Logistic regression, analysis of variance, and Pearson's correlation were performed in SAS (2003) version 6. Overall AMU practice scores were above 50% despite detecting violation of manufacturer's specifications. AMU was correlated with farmer's knowledge, r (178) = 0.42, p =0.000 and attitude, r (178) = 0.54, p =0.000. Farming scale, type of livestock kept and level of education influenced AMU (P 0.05). Farming scale influenced above 50% of the farmers to change label dosages, withdrawal periods, treatment frequencies, and consult friends on AMU. A similar pattern was noted on the effect of main livestock species kept on changing treatment frequencies and the use of human antibiotics. AMU without prescriptions increased with a decreasing level of education (P = 0.010). Knowledge on AMU was high for LSCF (average 58%), low for A1 (average 33%), and SSCF (average 46%). Attitudes were positive for LSCF (average 67%) and SSCF (average 57%) and negative for A1 (average 49%). We concluded that there is a serious violation of antimicrobial manufacturer's specifications by farmers in the Chikomba district which is associated with poor knowledge and attitudes on prudent ways of AMU